Restricted Oxygen‐Deficient Basins on the Northern European Epicontinental Shelf Across the Toarcian Carbon Isotope Excursion Interval. Issue 6 (9th June 2021) - Wang, Yunfeng; Ossa, Frantz Ossa; Spangenberg, Jorge E.; Wille, Martin; Schoenberg, Ronny
Abstract: The worldwide recognition of the Toarcian carbon isotope excursion (T‐CIE) in organic‐rich sedimentary rocks has been linked to an oceanic anoxic event (OAE) which implies the world's deep oceans were anoxic ∼183 Ma. The majority of independent redox observations used to build this argument were mainly obtained from T‐CIE organic‐rich sediments deposited on northern European epicontinental shelf. However, increasing evidence has shown that this shelf had limited connection with the open ocean, making it unsuitable for reconstructing the T‐CIE ocean redox structure. To unveil such controversy, we present integrated δ 15 Nbulk and δ 15 Nker from Dotternhausen profile, Germany, combined with literature data from other T‐CIE profiles. Both δ 15 Nbulk and δ 15 Nker values are predominantly between +0.3 and +2.5‰. These positive near‐zero δ 15 N values imply enhanced N2 fixation by cyanobacteria using molybdenum (Mo)‐based nitrogenase to compensate bioavailable N loss following quantitative denitrification and/or anammox in a strongly redox‐stratified marine setting. Such N isotope composition contradicts the typical sedimentary δ 15 N values (>3‰) induced by partial water‐column denitrification and/or anammox in modern‐ocean oxygen minimum zones. We rather propose the existence of local oxygen‐deficient basins on northern European epicontinental shelf where dissolved N underwent extensive denitrification and/or anammox causing bioavailable N deficiency. Mo‐based diazotrophy thus played a critical role in discriminating N isotope compositions among multiple hydrographically restricted T‐CIE marginal basins. Restricted oxygen‐depleted environments on the northern European epicontinental shelf unlikely represent the open‐ocean redox landscape. The existence of the global OAE thus needs comprehensive redox investigations on Tethys and/or Panthalassa deep‐sea T‐CIE successions to validate. Key Points: Molybdenum‐based nitrogen fixation was prevalent in the northern European epicontinental shelf during the Toarcian carbon isotope excursion Quantitative denitrification and/or anammox caused nitrogen famine in strongly redox‐stratified environments during the early Toarcian Oxygen‐deficient basins on the northern European epicontinental shelf across the Toarcian carbon isotope excursion